The Role of Public Discourse in Threat Framing: The Case of Islamophobia in Czech Republic - Donatella Bonansinga (CES Working Papers, 2015)
Perception and interpretation of risks do not always come from a direct experience but are filtered by the mass media and political discourse. The message they spread and the interpretations of reality they suggest have a profound impact on the (mis)perceptions developed by citizens. Currently all over the European Union the Islamic threat, as linked to terrorism, is conceived and perceived as a fundamental threat to security. But is there a real threat? By means of a discursive analysis, this paper aims at exploring the dynamics of threat construction as related to the framing of Islam as an issue of security concern, by focusing on the role of public discourse and by providing some insights from Czech Republic (CZ). Czech Republic is an interesting case to study misperceptions, insecurity complexes and the manipulation of public discourse, as the percentage of Muslim population in the country is tantamount to zero but Islamophobic feelings are gathering momentum and rising consistently. The fundamental question driving the research aims at explaining why a country with a numerically negligible Muslim minority is experiencing growing public hostility, manifested through the raising mobilization of citizens against Islam. The hypothesis suggests that the exposure of public opinion to specific media representations and political rhetoric may induce misperception and the development of Islamophobic sentiments. The paper will firstly go through an overview of the literature on the topic; it will then analyze the general trends in Islamophobic discourse in CZ, through the lens of the securitization theory.
Keywords: 330; security; threat construction; Muslims; political discourse; islamophobia